Mastering the Microsoft Deployment Toolkit - Stokes, Jeff; Stokes, Jeff; Singer, Manuel (Packt Publishing, 2016)
Take a deep dive into the world of Windows desktop deployment using the Microsoft Deployment ToolkitAbout This BookLearn Microsoft Deployment Toolkit best practices and how to adopt them into your deployment projectTroubleshoot task sequence errors and quickly resolve deployment blockersAn easy-to-follow, in-depth guide to image creation, customization, and deployment of WindowsWho This Book Is ForThis book is ideal for those deploying or planning to deploy Windows, in need of a top-to-bottom guide on project deployment. It is also an invaluable resource for consultants who need a top-to-bottom guide (or just a refresher) on project deployment.What You Will LearnBuild a production-ready MDT environmentAdminister the environment for multiple usersCustomize your reference image with an MDT Task SequenceCreate standalone media for offline deploymentsCustomize the default user profile according to the version of WindowsGet to grips with some troubleshooting steps and processes to reduce the time for recovery of a failed imageCustomize and create Windows images for deploymentDiscover useful tips and tricks to help save time in your deployment projectsIn DetailThe Microsoft Deployment Toolkit (MDT) provides a comprehensive collection of tools, processes, and guidance for automating desktop and server deployments. It considerably reduces deployment time and standardizes desktop and server images. Moreover, MDT offers improved security and ongoing configuration management. Microsoft Deployment Toolkit is the official supported method of creating and customizing Windows images for deployment.Starting from scratch, this book walks you through the MDT setup, task sequence creation, and image deployment steps in detail. Breaking down the various MDT concepts, this book will give you a thorough understanding of the deployment process.Beginning with imaging concepts and theory, you will go on to build a Microsoft Deployment Toolkit environment. You will understand the intricacies of customizing the default user profile in different versions of Windows. Driver handling can be a challenge for larger organizations; we'll cover various driver concepts including mandatory driver profiles. ]Other important topics like the User State Migration Tool (USMT), configuration of XML files, and how to troubleshoot the USMT are also discussed in the book.We will cover the verifier and Windows Performance Toolkit for image validation scenarios. Furthermore, you will learn about MDT web frontend implementation as well as how to utilize the database capabilities of MDT for deeper deployment options. We'll wrap it all up with some links to resources for more information, blogs to watch, and useful Twitter handles.Style and approachThis is a comprehensive guide written using a step-by-step approach. It begins with the basics and gradually moves on to the advanced topics MDT.